Efficacy of bacteriophage and organic acids in decreasing STEC O157:H7 populations in beef kept under vacuum and aerobic conditions: A simulated High Event Period scenario. (April 2020) - Shebs, E.L.; Lukov, M.J.; Giotto, F.M.; Torres, E.S.; de Mello, A.S.
Abstract: After High Event Periods, beef subprimals are usually removed from vacuum and treated with antimicrobials. After re-packaging, subprimals are tested to verify the presence of STEC. In this study, bacteriophage and organic acids were applied on beef contaminated with STEC O157:H7 to evaluate the efficiency of industry practices. Beef samples inoculated with STEC were treated with bacteriophage, lactic acid, and peroxyacetic acid and kept under vacuum or aerobic conditions. STEC loads were evaluated 30 min and 6 h after antimicrobial applications. Under aerobic conditions for 30 min and 6 h, phage reduced STEC in beef by approximately 1.4 log whereas organic acids led to a 0.5 log reduction. Under vacuum for 30 min, bacteriophage significantly reduced STEC by 1 log. No effects were observed when samples were treated with organic acids. Under vacuum after 6 h, bacteriophage reduced STEC loads by 1.4 log, lactic acid reduced by 0.6 log, and no effects were observed when peroxyacetic acid was applied. Highlights: Lactic acid minimally reduced E. coli in vacuum-packaged beef. Peroxyacetic acid did not reduce E. coli in vacuum-packaged beef. Bacteriophages EP 75 and EP 355 led to the best E. coli reduction in vacuum-packaged beef. Bacteriophages led to improved reductions of E. coli in aerobically-packaged beef. Bacteriophage applications are more effective than organic acids.